Ways to improve the organization of tax accounting in the republic of kazakhstan - Sarinova, A. E. (Journal of Economic Research & Business Administration, 2016)
Efficient tax accounting plays an important role in a positive financial situation of the enterprise. Optimize revenue and reduce expenses for cor porate income tax and other obligatory payments is the main goal of every entrepreneur. So today the topic of improving tax reporting actual entre preneurs and subjects of economic activities. This article lays out the tools to create preconditions for the formation of an effective tax accounting in the enterprises of the country. In the article stimulating tax instruments and their effective use thus far justified the author’s vision.